2021
DOI: 10.1038/s43247-021-00223-6
|View full text |Cite
|
Sign up to set email alerts
|

Conservation agriculture increases the soil resilience and cotton yield stability in climate extremes of the southeast US

Abstract: Climate extremes pose a global threat to crop security. Conservation agriculture is expected to offer substantial climate adaptation benefits. However, synergistic effects of conservation practices on yield during normal versus extreme climates and underlying regulatory mechanisms remain elusive. Here, we analyze 29-years of climate data, cotton (Gossypium hirsutum L.) yield, and soil data under 32 management practices in Tennessee, USA. We find that long-term no-tillage enhanced agroecosystem resilience and y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 45 publications
2
8
0
1
Order By: Relevance
“…(24) demonstrated that fine root production and decay in cornbased systems influence labile pools of C and N more so than processed pools of C. However, soil C cycling under contrasting management juxtaposed with intense climatic conditions is largely unknown at the field scale. Numerous studies have demonstrated that increases in soil organic matter contribute to yield stability in drought conditions (25)(26)(27)(28). Additionally, Acosta-Martıńez etal.…”
Section: Introductionmentioning
confidence: 99%
“…(24) demonstrated that fine root production and decay in cornbased systems influence labile pools of C and N more so than processed pools of C. However, soil C cycling under contrasting management juxtaposed with intense climatic conditions is largely unknown at the field scale. Numerous studies have demonstrated that increases in soil organic matter contribute to yield stability in drought conditions (25)(26)(27)(28). Additionally, Acosta-Martıńez etal.…”
Section: Introductionmentioning
confidence: 99%
“…In NT, there is also a greater volume of mesopores, contributing to greater water retention [11]. Thus, it is characterized as a system with greater water stability, offering less risk to production due to drought [1,14].…”
Section: Introductionmentioning
confidence: 99%
“…Other current research on soil resilience also focuses on management practices and climate regimes. These include investigating positive impacts from land management practices due to the effects of ecological intensification [44] and also research into enhanced agrisystem resilience and production stability in climate regimes [45]. Specifically in the New Zealand context, recent research includes a focus on frameworks of soil and landscape functionality which can assist in land management considerations, termed "the Land Resource Circle".…”
Section: Allocated Class and Association With Soil Typementioning
confidence: 99%